Peningkatan Kapasitas Komunikasi Pemasaran dan Kewirausahaan Digital Berbasis Artificial Intelligence (AI) pada Siswa Jurusan Kriya Kreasi Batik dan Tekstil SMKN 14 Bandung - Haris Annisari Indah Nur Rochimah; Rana Akbari Fitriawan; Amanda Bunga Gracia; Nanda Priatna; Syahira Malva Anadea; Fakhri Athar Radhian; Muhammad Akmal Irhamna (Elevasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
The regeneration of Indonesian batik artisans faces challenges in business sustainability and digital marketing development. As results from field observations of students majoring in Batik and Textile Creative Crafts at SMKN 14 Bandung show a gap between technical batik competencies and marketing communication competencies, foremost in narrating product values, identifying market, and building self-entrepreneurship capacity as Batikpreneurs. This phenomenon causes the inability of cultural creative products to compete in the digital ecosystem. The community service program entitled "Batikpreneur for Youth Generation: Improving Marketing Communication Capacity and Digital Entrepreneurship Based on Artificial Intelligence (AI) for Students majoring in Batik and Textile Creative Crafts at SMKN 14 Bandung" is a solution in increasing marketing communication literacy and the use of artificial intelligence technology for students. This program emphasizes the development of student competencies in Brand Storytelling, Persuasive Communication, and the use of Artificial Intelligence (AI) as a supporting tool for communication strategies using the Participatory Action Learning (APL) approach. Program implementation includes: (1) Utilization of AI for audience research and market trends; (2) Strategy for creating authentic brand narratives; and (3) Application of AI-Assisted Copywriting techniques to produce product descriptions that are both emotionally valuable and Search Engine Optimization (SEO) friendly. This activity is in line with the 2026 Humanities and Media Studies Expertise Group Community Service roadmap with the theme, “AI, Creativity, and Media Innovation”. Through the integration of technology in empowering the creative economy, this activity is expected to produce adaptive young entrepreneurs. The output targets of this activity include practical guidance, as well as the publication of scientific articles in Sinta-accredited national journals as a scientific contribution in the field of digital marketing communications.